Pandemi dan Ruang Kelas Dunia Maya - Nunung Nurfajri Ainun (Universitas Negeri Makassar, 2021)
This article purposes and describe about classrooms situation that move through online class, at the primary school level in Bone district. The situations that force everyone to adapt with a network learning system, giving a different experiences and meanings in each school, parent and students. This research article conducted at two elementary schools in Bone district, for two weeks starting on March 29 to April 12, 2020 with descriptive qualitative research methods, the informants were chosen based on snowball techniques, to five informants. The informant is considered to be able to give an idea about virtual classrooms were in the pandemic. Interviews conducted by chatting and in direct interview. Research data is also supported by chat in 'virtual classrooms', and literature. The results showed that there were two groups of virtual classes during this pandemic, namely, 1) Parents as the center, in cyberspace classes during this pandemic, The parent becomes the center of learning process, because the teacher communicates to students through the parent intermediary. 2) Parent become leaders where parent act as a teachers who teach and explain material to their children, 3) Parent become associate, where teaching and learning activities are still carried out by the teacher through learning videos, video links to voice notes, so that parent only act as student associate. These findings, of course, are influenced with the facilities and infrastructure prepared by the school. School support, creativity and teacher initiative and the role of parent became the movers of the virtual world class during this pandemic.Keywords: home school, pandemic, elementary school, virtual classrooms, parents.